Pressupostos teóricos da perspectiva CTS (Ciência, Tecnologia e Sociedade) no contexto de cursos de graduação a distância - Leite, Ana Cláudia de Oliveira (Universidade Federal de São Carlos, 2011)
Each season brings new trends that influence the culture, economy and technology derived from the growth and development of society. Thus, after 90 years of the twentieth century saw the beginning of a period called the information age, characterized by globalization and the importance of intellectual capital, knowledge generation and sharing and use of information and communication technologies. In Brazil, among the changes that have occurred is the increase in offering distance learning courses: the federal government uses distance learning as a way to democratize access to public education, free high-quality, private institutions enjoy the opportunity to expand their areas of expertise and gain more and more students, and organizations envision the possibility of training and qualification of its professionals. The university, in turn, as a developer of the great centers of science and technology (S&T) also started to adopt distance learning as part of the plan of public policies for continuing education in Brazil. In this scenario, there is a broadening of debate about the fruits of experience in various fields of knowledge. The Movement for Science, Technology and Society (STS), whose roots date back to mid-twentieth century, seeks to demystify the S&T and public participation in decision making. From the vision of this movement, distance learning favors the acquisition of student autonomy as a subject of the learning process through collaborative action, to intervene directly in building a sustainable society. Offer subsidies to students to discuss scientific and technological issues that permeate the society, leading them to understand the social dimension of S&T, both in terms of their social background, as his social and environmental consequences. During this study, we used the method of hypothetical-deductive approach, the method of procedure and techniques of monographic literature search and content analysis, whose presentation and discussion of results are organized into seven chapters. In none of the pedagogical projects directly quoted the STS perspective on its structure, yet it is evident the presence of the indirect influence of this movement. By analyzing the results, it was found that the educational proposals of the courses offered by UAB/UFSCar allow students a better understanding of S&T as results of human knowledge socially constructed in order to complete their training as citizens. In this study, was also observed that the pioneering spirit and innovative vision of the project UAB/UFSCar, present in the educational proposals of undergraduate courses at a distance, may reveal and/or anticipate trends in distance learning in Brazil, contributing to its growth and scientific, technological and social development.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Ensino a distância; Ensino superior; Projeto pedagógico; Distance learning; Higher education; Pedagogical project; Science, Technology and Society (STS); CIENCIAS SOCIAIS APLICADAS